Analysis and Applications of Mathematical Fluid Dynamics (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The reprint contains 19 articles that have been accepted and published in the Special Issue “Analysis and Applications of Mathematical Fluid Dynamics, 2023” of MDPI’s Mathematics journal, which covers a wide range of topics related to experimental and theoretical fluid flow processes and the analysis of heat flow in stockpiles of reactive materials. Among others, these topics include the following: applied, computational, and mathematical physics; combustion and decomposition theories; computational thermal engineering; heat and mass transfer; magnetohydrodynamics (MHDs); mechanics of fluids; and numerical methods. This collection is open to researchers in mathematical modeling using numerical methods to solve complicated differential equations related to Navier–Stokes equations. The reprint will hopefully be of interest and of use to those working in the field of Mathematical Modeling and Computational Fluid Dynamics.